Age-Related Changes in Protein Binding of Drugs: Implications for Therapy - Grandison, Monica K.; Boudinot, F. Douglas (Clinical pharmacokinetics, 2000)
The plasma protein binding of drugs, particularly those that are highly bound, may have significant clinical implications. Although protein binding is a major determinant of drug action, it is only one of a myriad of factors that influence drug disposition. The extent of protein binding is a function of drug and protein concentrations, the affinity constant for the drug-protein interaction and the number of protein binding sites per class of binding site. Age-related changes in protein binding are usually not clinically important in drug therapy. Albumin levels are generally decreased in the elderly, whereas alpha1-acid glycoprotein levels are not altered by age per se. Alterations in plasma protein binding that occur in the elderly are generally not attributed to age, but rather to physiological and pathophysiological changes or disease states that may occur more frequently in the elderly and most often account for altered protein binding. Age-related physiological changes, such as decreased renal function, decreased hepatic function and decreased cardiac output, generally produce more clinically significant alterations in drug disposition than that seen with alterations in drug plasma protein binding. An understanding of the inter-relationships between drug concentrations, protein binding, the physiology of aging, disease, pharmacokinetics and pharmacodynamics is necessary for effective therapeutic monitoring. Monitoring of unbound drug concentrations simplifies these relationships and provides the fundamental information needed for dosage regimen development and adjustment. Drug therapy in the elderly should be individualised taking into account all of these factors.